Thermoelectric properties of Ag-doped CuS nanocomposites synthesized by a facile polyol method. Issue 8 (9th February 2018) - Tarachand,; Hussain, S.; Lalla, N. P.; Kuo, Y.-K.; Lakhani, A.; Sathe, V. G.; Deshpande, U.; Okram, G. S.
Abstract : Single crystalline hexagonal nanodisks (NDs) of covellite CuS and temperature dependent thermoelectric figure of merit of Ag-doped CuS nanocomposites. Abstract : We report the first thermoelectric properties of Cu1− x Ag x S, x = 0–0.75 nanocomposites, synthesized by using a facile polyol method. Systematic characterizations using powder XRD, Rietveld refinement of XRD, EDAX, XPS and Raman spectroscopy confirmed their single phase, hexagonal crystal structure with the space group P 63 / mmc, nominal elemental composition, valence states of the constituent elements and stoichiometric nature. The TEM images showing the CuS formation of nearly perfect hexagonal disk-like particles of average thickness 26.7 nm and breadth ranging in a few hundreds of nanometers with nanorods stacked from these hexagonal nanodisks (NDs) elongated along the c axis corroborate the FESEM images. Attributed to structural phase transition, an anomaly at 55 K is clearly observed in both the thermopower and Hall resistivity data. By increasing x, a systematic reduction in thermal conductivity was observed near 300 K. Consequently, a 50% enhancement in figure of merit was observed for Cu0.9 Ag0.1 S as compared to pure CuS at 300 K. These results therefore are expected to provide a new direction in improving ZT near 300 K.